Textos hispánicos neolatinos conocidos en la cultura impresa cracoviana del siglo XVII (a partir del ejemplo de la imprenta Schedels) - Czerenkiewicz, Michał (Cuadernos de Filología Clásica. Estudios Latinos, 2020)
This paper examines Spanish-Polish literary connections in 17th and in the beginning of 18th century by the example of the reception of some Neo-Latin works addressing Spanish issues which were acquired in the editorial production of the Schedels printing shop. The officina Schedeliana operated in early modern Cracow (1639-1708) and was one of the most significant printing offices in the Polish-Lithuanian Commonwealth in those times. The paper points to the books which reflect cross-cultural impact of both the Latin language and Spanish themes and were published by the specific printing house. Some of the branches of works printed by the Schedels were translations and editions of Neo-Latin texts which concerned Spanish leading figures of the Post-Tridentin period. The reception of key ideas and values present in the 17th century selected Neo-Latin literary output addressing Spanish issues is investigated, as well as the traces of awareness of the famous Spaniards in the books released in Cracow. En este artículo se examinan las conexiones literarias hispano-polacas del siglo XVII y principios del XVIII a partir del ejemplo de la recepción de algunas obras neolatinas sobre temas españoles adquiridas en la producción editorial de la imprenta Schedels. La officina Schedeliana operó en la Cracovia moderna temprana (1639-1708) y fue una de las oficinas de impresión más importantes de la Commonwealth polaco-lituana en aquellos tiempos. El artículo llama la atención sobre los libros que reflejan el impacto transcultural de los temas tanto en lengua latina como española y que fueron publicados por esta imprenta en particular. Algunos de los ámbitos de las obras impresas por los Schedels fueron traducciones y ediciones de textos neolatinos que se referían a las principales figuras españolas del período postridentino. Se investiga la recepción de ideas y valores clave presentes en la producción literaria neolatina seleccionada del siglo XVII que aborda la problemática española, así